Quercetin reduce cardiomyocytes damage in type 2 diabetic rats - Asri Hendrawati; Nadhir Nadhir (Universa Medicina, 2014)
BACKGROUNDDiabetes mellitus (DM) is a group of metabolic diseases which are characterized by hyperglycemia, resulting in various complications. A major macrovascular complication of DM is cardiac failure due to cardiomyopathy. Hyperglycemiaincreases oxidative stress, so an oxidative-stress reducing therapeutic agent is required, e.g. the antioxidant quercetin. The aim of this study was to assess the effects of quercetin in reducing damage to cardiomyocytes of type 2 diabetic rats.METHODSThis research is an experimental study using 40 rats. With simple randomallocation, rats were divided into eight groups, then type 2 diabetes mellituswas induced using streptozotocin (5 rats per group). The test material wasquercetin given at doses of 5, 20 and 80 mg/kgBW/day orally for 4 weeks.Each single dose of quercetin was given in combination with glibenclamide 5mg/ kgBW/day. After 4 weeks the rats were decapitated and the cardiac tissuestaken to quantify the percentage of cell damage after hematoxylin-eosin staining(HE).RESULTSQuercetin at a dose of 80 mg/kgBW/day can lower cardiomyocyte damagebetter than quercetin at doses of 5 or 20 mg/kgBW/day. A combination ofquercetin and glibenclamide can significantly lower levels of cardiomyocytedamage better than quercetin without glibenclamide (p<0.05).CONCLUSIONQuercetin at a dose of 80 mg/kgBW/day with or without glibenclamide canlower damage to cardiomyocytes of type 2 diabetic rats. Thus quercetin mightserve as a valuable protective agent in cardiovascular inflammatory diseasesin diabetic rats.